Expectation horizons of the Finnish top level olympic sport actors at the start of the high performance unit's operational work - Nirkko, Tapio; Päkk, Robert (2014)
Sport in Finland has gone through a major change process. Re-structuring and re- organizing by governmental researchers and the HUMU (Huippu-urheilun muutos, Top level sport change) have ended with the proposal of a new system and new programmes within Finnish sport. The present study examined the current situation in the Finnish elite sport sphere using semi-structured expert interviews. The interviews concentrated on the experiences of the HUMU group’s work, understanding of the definitions used in the HUMU group’s final report and the expectations created towards the HUY (Huippu- urheiluyksikkö, Unit of High-Performance Sport). The interview data was analysed to create an overview of the three expert groups’ evaluation of the work done and their expectation horizons towards the HUMU work. Thus, this qualitative case study aimed at investigating the understanding of HUMU reports from the viewpoint of three different parties in Finnish elite sport – HUY, athletes and coaches. A hermeneutic analysis of the semi-structured expert interviews with the three different parties was conducted to find the strengths and weaknesses of the new proposed system as well as to get an understanding of the participants’ views on the matter; and to investigate the expectations horizon of the three parties, relating to the future work of HUY. The participants were key representatives of Finnish elite sport: coaches (2), athletes (3) and the representative of the HUY (1). Semi-structured interviews were conducted in Finnish and lasted approximately 30 to 75 minutes; the interviews were conducted in February, March and April of 2013. Results indicated that there was a generally good understanding and satisfaction with the work done by the HUMU group. Despite that, difficulties arose defining some of the terms presented in the HUMU final report. The findings show that there is a lack of information for consensus in the discourse of top- level sport in Finland. The results suggest that ambiguity in the meaning of specific terms create obstacles in reaching consensus. Overall, the expectation horizons of the HUY group’s work are positive as a whole, and the results of the work done so far is expected to reflect after the next two Olympiads. Future studies should further investigate the discourse regarding the definitions of the terms used in the HUMU final report and the resulting understanding of them among different parties.